The effects of ketone bodies and ketogenesis on the PI3K/AKT/mTOR signaling pathway: A systematic review - Azlinah Matawali; Jia Wen Yeap; Shaida Fariza Sulaiman; Mei Lan Tan (Elsevier, 2025)
Ketogenesis and the PI3K/AKT/mTOR pathway are linked to metabolic imbalance and dis- ease progression. While ketone metabolism and mTOR inhibition are mechanistically con- nected, their functional relationship across disease models remains unclear. Although ke- togenesis can be induced by ketone ingestion, ketogenic diet, or fasting, their individual effects on this pathway require further clarification. This study systematically reviews the relationship between ketogenesis and PI3K/AKT/mTOR signaling, following PRISMA guide- lines across 3 databases. Eligible studies that met the selection criteria were evaluated using